A STUDY OF STUDENTS’ PERCEPTION AND LEVEL OF STUDENT MASTERY OF ONLINE LEARNING IN THE SCHOOL OF CIVIL ENGINEERING, UITM PAHANG - Normadiana Mohammad Hanapi; Mohd Mawardi Mohd Kamal (Journal of Islamic, Social, Economics and Development, 2022)
The COVID-19 pandemic has created a new phenomenon where technology and the internet are no longer an option but a necessity, especially in the field of education. This can be seen where almost all the teaching and learning (T & L) processes have been implemented online. Therefore, this study aims to explore the impact of the COVID-19 pandemic on the perception and level of student mastery at the School of Civil Engineering in terms of knowledge and facilities for the online learning process. This study used a set of questionnaires as an instrument for the data collection process. The respondents consisted of 114 students who attended the Diploma in Civil Engineering programme at the School of Civil Engineering, UiTM, Jengka Pahang Branch. The data obtained from this questionnaire was analyzed using the Statistical Package for the Social Sciences (SPSS) version 28. Descriptive statistics are used to analyze the relevant data and answer the questions of the study. As a result of the analysis of the data for the Cronbach Alpha trust test, the value obtained was equal to 0.897> 0.7. This shows that the instrument is in good condition as well as effective and can be used in this study. Based on the results of the study, video recording is the student's preferred learning medium (mean = 4.11). The findings also show that there is a relationship between the aspect of knowledge and convenience (the value of sig =.001< 0.05) and the correlation value of 0.535, which means a strong relationship between the two variables.